WOMEN STRUGGLE: A CRITICAL ANALYSIS OF WOMAN AT POINT ZERO AND THE COLOR PURPLE - Quyoom, Sundus (PEOPLE: International Journal of Social Sciences, 2017)
Women across the globe face the discrimination based on gender which not only leaves a physical scar on their bodies but a mental scar as well which is hard to erase. Women have realised their importance and they have been fighting for their rights from long back and it is still prevalent as it has not been achieved yet. The discrimination against women is an old story now and it differs from country to country. Emma Watson, a well-known English actress in her UN speech initiated a new step by launching a campaign known as He or She campaign as according to her it is important to include men for the fight of women emancipation. This wave of feminism is prevalent across the world including the Third World countries as well. Nawal El Saadawi in her book Woman at Point Zero beautifully portrays the condition of Egyptian women particularly Firdaus who is the main protagonist of the novel. This novel is based on a true event where Nawal met Firdaus in a jail who was a criminal and was soon to be hanged for the murder which she has committed. The interesting thing was that Firdaus was not appealing for life time imprisonment instead of death penalty and demanded death. Nawal got very curious to know about her life and finally Firdaus narrated her whole life story which was full of sufferings and struggle done to her by the men in her life and the society. Actually Firdaus was tired of this male dominated society and death was the only source of emancipation for her. On the other hand Alice Walker, a well-known Afro American writer in her book The Color Purple depicts the life of Celie who is an African woman whose life was also full of hardships and discrimination. But Celie survived all the harsh situations of her life which included mostly her domestic life and finally found her emancipation. The researcher in this paper by using comparative and analytical methodology is trying to build a bridge to fill the gap that women no matter of what country or race belongs, is connected to each other through the pain which is caused discrimination based on gender. It is interesting to note that both the protagonists through the end found their emancipation in their own ways.